2015
DOI: 10.1007/s00787-015-0703-7
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms in the relation between GABRA2 and adolescent externalizing problems

Abstract: Conduct problems, alcohol problems and hyperactive–inattentive symptoms co-occur at a high rate and are heritable in adolescence. The γ-aminobutyric acid A receptor, α2 gene (GABRA2) is associated with a broad spectrum of externalizing problems and disinhibitory-related traits. The current study tested whether two important forms of disinhibition in adolescence, impulsivity and sensation seeking, mediated the effects of GABRA2 on hyperactive–inattentive symptoms, conduct problems, and alcohol problems. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 68 publications
(147 reference statements)
3
12
0
Order By: Relevance
“…A SNP is a variation in a single base pair within DNA. Genetic main effects for individual SNPs exist for impulsivity and related behaviors (Hamidovic, Dlugos, Skol, Palmer, & de Wit, 2009; McGue et al, 2013; Villafuerte, Strumba, Stoltenburg, Zucker, & Burmeister, 2013; Wang, Chassin, Geiser, & Lemery-Chalfant, 2015). More recently, studies have combined multiple SNPs into indices of genetic predisposition, known as polygenic risk scores.…”
Section: Impulsivity In Genetically Informed Researchmentioning
confidence: 99%
“…A SNP is a variation in a single base pair within DNA. Genetic main effects for individual SNPs exist for impulsivity and related behaviors (Hamidovic, Dlugos, Skol, Palmer, & de Wit, 2009; McGue et al, 2013; Villafuerte, Strumba, Stoltenburg, Zucker, & Burmeister, 2013; Wang, Chassin, Geiser, & Lemery-Chalfant, 2015). More recently, studies have combined multiple SNPs into indices of genetic predisposition, known as polygenic risk scores.…”
Section: Impulsivity In Genetically Informed Researchmentioning
confidence: 99%
“…The literature between 2000 and 2007 showed that more attention was paid on GABRA2 and CHRNA5. The risk of GABRA2 mutations in adolescents produced externalizing problems to the development of problematic alcohol and drug use by multiple pathways (42,43). Variants in GABRA2 are associated with alcohol and nicotine dependence, representing an early risk factor to the problematic alcohol or drug use (42,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, associations between GABRA2, AD (Edenberg et al 2004; Lappalainen et al 2005; Covault et al , 2004; Drgon et al ., 2006; Fehr et al ., 2006; Soyka et al 2008; Enoch et al 2006, 2010; Roh et al 2011), drug dependence (Agrawal et al 2006; Enoch et al 2010; Ehlers & Gizer 2013), and externalizing behavior (Dick et al, 2013; Salvatore et al, 2015; Trucco et al, 2016; Wang et al, 2016) have been observed, indicating the potential of genetic studies of beta EEG to facilitate discovery of genes underlying disinhibitory behavior. However, the number of replicable genetic variants uncovered by this approach has been limited (Iacono et al, 2016), necessitating large scale genetic association studies of beta EEG utilizing the best-practices of genetic epidemiology.…”
Section: Discussionmentioning
confidence: 99%